Assessing gas and oil resources in the intermountain West : review of methods and framework for a new approach - LaTourrette, Tom, 1963- (MR (Series) ;, 2002)
This work examines four traditional assessments of the nation's potential supply of natural gas and oil resources. It suggests a new methodology - estimating "viable" resource, infrastructure and transportation costs. Environmental impacts are also considered